Efficacy and safety of microwave ablation for treatment of follicular thyroid neoplasms: a preliminary study - Xin-Yi Zhou; Xin-Yu Yu; Ying Wei; Zhen-Long Zhao; Li-Li Peng; Yan Li; Jie Wu; Shi-Liang Cao; Ming-An Yu (International Journal of Hyperthermia)
Objective To assess the feasibility, efficacy, and safety of microwave ablation in treating follicular thyroid neoplasms and suspicious follicular thyroid neoplasms.Methods In this retrospective study, the data of patients treated with microwave ablation for follicular neoplasms from December 2016 to January 2024 were summarized. The changes in nodule size, volume, technical success rate, disease progression, complete tumor resolution, thyroid function, and complications post-ablation were evaluated.Results Seventy-four patients (15 men, 59 women; mean age 46.3 ± 15.2 years) with follicular neoplasms were included. Over a median follow-up of 13 months, complete ablation was achieved, giving a 100% technical success rate. At the first month post-ablation, the maximum diameter of nodules showed no significant change (p = 0.287). From the third month, both maximum diameter and volume significantly decreased (p < 0.005 for all). Volume reduction rates remained stable at one and three months (p = 0.389 and 0.06, respectively) but increased significantly thereafter (p < 0.005 for all). By 24 months, the median maximum diameter had reduced from 2.3 cm to 0 cm, achieving a median volume reduction rate of 100%. Nodules disappeared completely in 20.3% (15/74). Local recurrence was noted in 2.7% of cases (2/74), with no metastasis or neoplasm-related deaths reported. Thyroid function remained unchanged post-treatment (p > 0.05). The complication and side effect rates were 8.1% and 4.1%, respectively.Conclusions Initial findings suggest microwave ablation is an effective and safe treatment for follicular neoplasms, with low incidences of disease progression and complications, while maintaining thyroid function.